Preparatory study for the evaluation of Denmark's development cooperation on climate change adaptation - Lily Salloum Lindegaard; Mikkel Funder; Esbern Friis-Hansen (Danish Institute for International Studies (DIIS), 2021)
This working paper presents the outputs of the Preparatory Study for the 2019 Climate Evaluation, commissioned by the Evaluation Department (EVAL) of the Danish Ministry of Foreign Affairs.The Preparatory Study provides information on Danish support to climate change adaptation in developing countries. Its objective was to support an evaluation of Danish climatechange funding to developing countries from 2008to 2018, especially support to climate change adaptation. Specifically, the study sought to help frame the scope of the evaluation; identify potential country case studies, case projects and evaluation themes; and point out overarching issues for further reflection. To do so, it provided overviews of all Danish climate change adaptation-related Official Development Assistance (ODA) from 2008 to 2018 and of adaptation support through the Danish Climate Envelope, which provides Fast Start Finance for climate change mitigation and adaptation in developing countries. In addition to providing an overview of Danish adaptation finance, the study described the methodology used in the evaluation and the particular aspects of Danish adaptation support to be taken up in the evaluation. This included support provided throughNGOs and multilateral funds, with suggestions for NGOs that could be included in the evaluation and an overview of the relevant evaluations of multilateral funds supported by Danish finance. In addition, the study suggested possible themes for evaluation, overarching questions regarding supportto adaptation generally, and trends, gaps and other considerations regarding Danish adaptation support specifically.
Keywords: 330; Climate change and environment; Inequality and poverty; Development in practice